Hubungan Pengetahuan Ibu, Pendidikan Ibu dan Dukungan Suami dengan Praktek Pemberian Asi Eksklusif di Kelurahan Muktiharjo Kidul Kecamatan Telogosari Kota Semarang - Agus Sartono; Hanik Utaminingrum (Jurnal Gizi, 2012)
Exclusive breastfeeding is recommended for the mother in order to get the optimal growth and development of the baby. Nevertheless, the health profile of Central Java in 2008 showed coverage of exclusive breastfeeding is only about 28.96%.. The caverage of exclusive breast feeding in Semarang Manicipality in 2006 is 40.07% and the year 2007 decreased to 38.44%. This figure is still very low when compared with nasional exclusivebreastfeeding target of 80% in 2010 South Muktiharjo village is part of Semarang region. Some of studi, showed that the exclusive breast feeding practice related with social economic factor, mother’s work status, formula milk advertisement, and the role of health provider, especially who have direct role in maternal health. Besides that,the husband’s support, mother’s ability of exclusive breast feeding, and mother’s education, guessed related with exclusive breastfeeding practice. Objective of this study is to analyze the correlation between mather.s ability, mather’s education and support her husband with theexclusive breastfeeding practice in South Muktiharjo Village, Semarang City.The study is cross sectional. The analysis unit and respondet in the study was mother who had infants aged 6-12 months at Muktiharjo Kidul Village, Semarang City. The numbering of mothers who fill criteria 158 persons. The number of samples 62 mothers, to be taken with simple random sampling. Data were collected by interview using a questionnaire. Analysis of the correlations between variables, was done with multi plelogistic regression.The result of studi showed only 9 mothers (14,5 %) who exclusive breast feeding. 46 mothers (72,4 %) have low ability of exclusive breas feeding although 79,2 % mothers SMP graduation or more.. Only 14 husbands (22,6 %) support mothers breast feed the baby.There are no correlations between the three variables studied (mather’s ability, mother’s education and support of her husband) with exclusive breastfeeding practice, together all of independence variables or part one by one.Keywords: exclusive breastfeeding, maternal knowledge, maternal education, husband's support